Religious-Nationalist Character Building Model on Pondok Pesantren based School to Reduce Radicalism in Kendal Regency, Central Java Provinces - ., Sriyanto; Kurniawan, Edi; Suharini, Erni; Junior Trimasukmana, Danang (International Journal of Engineering and Technology, 2018)
Globalization has made the boundaries between countries and territories are blurred, this is due to the increasing of the population transfers between regions of the state. This condition makes the positive mean taken as easy to find cooperation network and job opportunity, but on the other hand also become a threat to the integrity of a country. The threat generally comes from the many ideologies and cultures that enter into a country, thus undermining the ideology of the country of origin. The main objective of the research is to develop a model of religious nationalist characteristic of schools based on boarding schools, like the pondok pesantren where the model can be accepted as an educational medium to reduce radicalism in Indonesia that usually under the guise of religion. The research uses research and development method which is preceded by observation,and interviews with students, cottage and school managers, and stakeholders of pondok pesantren in pesantren based school in Kendal Regency to know the condition of social life and there policy, and then create database. The main outcome of this study is the guidebook on the model of religious nationalist characterization, which is expected to be a new innovation in character building strategies in pesantren-based schools that are expected to answer the challenge of danger of radicalism under the guise of religion. It also produced scientific articles published in international and national journals as an effort to socialize the model.Â Â